Between Discipline and Interdisciplinarity: Remarks on the Methodological Status of Cultural Studies - Walczak, Monika (Roczniki Kulturoznawcze, 2010)
The paper addresses the methodological status of Polish cultural studies. It consists of two parts: the first is factual and the second theoretical and methodological, reflecting on theses held by culture scholars on their own area with the use of general methodological knowledge. In the first part I give an account of the different names (nomenclature) for cultural studies and of the traditions they refer to. I point out disciplines that are included in cultural studies, giving examples of selected Polish cultural studies centers. In the second part, on the basis of methodology, I explicate the meaning of the methodological categories that culture scholars themselves consider adequate to a description and an explanation (an understanding) of the methodological status of cultural studies (such as notions of “scientific discipline”, “interdisciplinary studies”, “integration”, etc.). I note the incompatibility between the institutional status of cultural studies and their methodological status, and I point out some sources of the incompatibility and its consequences. Indeed, cultural studies were created as an academic discipline in Poland, but from the methodological point of view they are interdisciplinary rather than a separate discipline. The reasons for this can be found in the methodological criteria cultural studies fulfills and fails to fulfill and in the methodological self-consciousness of culture scholars themselves. I note that the emergence of cultural studies is an expression of the unifying tendencies in science. Therefore, the methodological self-knowledge of cultural studies should be developed by realizing how rich in aspects and dimensions the integration of the sciences phenomenon is, and consequently, how many types of interdisciplinary studies there are.